Pengaruh Obedience Pressure, Independensi, Dan Keahlian Audit Terhadap Audit Judgment Pada Kantor Akuntan Publik Di Wilayah Surabaya Timur. - Rieza Wardah Alawiyah; Tituk Diah Widajantie (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
This study aims to determine the effect of Obedience Pressure, Independence, and Audit Expertise on Audit Judgment at Public Accounting Firms in the East Surabaya Region. The population of this research is all auditors who work at the Public Accounting Firm in the East Surabaya Region which consists of 28 Public Accounting Firms that are registered in the Public Accounting Firm Information System at the Indonesian Institute of Public Accountants with the Ministry of Finance of the Republic of Indonesia Secretariat General of the Center for Financial Professional Development. These are 40 auditors who work at 9 Public Accounting Firms in the East Surabaya Region. This study uses the Structural Equation Model (SEM) model with the Partial Least Square (PLS) analysis model to test the previously proposed hypotheses. PLS analysis was tested using SmartPLS version 2.0 for windows software. Based on the results of the research that has been done, it can be concluded as follows: that Obedience Pressure on Audit Judgment is proven to have a significant negative effect. Independence from Audit Judgment is proven to have a significant positive effect. Audit expertise on Audit Judgment is proven to have a significant positive effect.